2021
DOI: 10.1136/bmjopen-2021-053268
|View full text |Cite
|
Sign up to set email alerts
|

Electronic reminders and rewards to improve adherence to inhaled asthma treatment in adolescents: a non-randomised feasibility study in tertiary care

Abstract: ObjectiveTo test the feasibility and acceptability of a short-term reminder and incentives intervention in adolescents with low adherence to asthma medications.MethodsMixed-methods feasibility study in a tertiary care clinic. Adolescents recruited to a 24-week programme with three 8-weekly visits, receiving electronic reminders to prompt inhaled corticosteroid (ICS) inhalation through a mobile app coupled with electronic monitoring devices (EMD). From the second visit, monetary incentives based on adherence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 28 publications
(26 reference statements)
1
34
0
1
Order By: Relevance
“…As detailed in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flowchart25 (see figure 1), searches identified 4268 articles; 8 met the eligibility criteria 26–33…”
Section: Resultsmentioning
confidence: 99%
“…As detailed in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flowchart25 (see figure 1), searches identified 4268 articles; 8 met the eligibility criteria 26–33…”
Section: Resultsmentioning
confidence: 99%
“…The first evaluated both gaming related incentives and financial incentives in a small population of minority adolescents, and found promising improvements in adherence and asthma control 16 . A more recently published pilot feasibility study showed potentially feasibility and acceptability of the intervention, 17 however there were significant technological challenges. Both studies recommended further randomized controlled trials of these incentive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…While promising for various diseases in the adult population, financial incentives have been comparatively under‐studied in children. There have been two small single arm feasibility studies of financial incentives in adolescents with asthma, which indicated further evaluation was warranted with a randomized controlled trial 16,17 . We therefore designed a randomized controlled trial to evaluate the effect of a modest financial incentive on medication adherence in adolescents with asthma as measured by an electronic medication monitoring device (EMM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to sending e-feedback and e-reminders to patients on regular basis, financial incentives were reported to enhance patient compliance 38 . In the context of the mobile application, a gaming component could be considered to further optimize compliance 39 , 40 . The efficacy of these methods in CAT patients needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%